Surveying the Impact of Services Marketing Mix Components (7Ps) on Patients' Disposition towards the Public & Private Hospitals of Sari City - Ghasem Abedi; Zeynolabedin Rahmani; Ehsan Abedini; Farideh Rostami (Tehran University of Medical Sciences, 2015)
Background: Services marketing mix (7Ps) is one of the most important concepts of management and marketing. This study has surveyed the role of services marketing mix components in patients` tendency towards the public and private hospitals in Sari. Materials and methods: In this cross-sectional study, 900 patients were selected from sari`s public and private hospitals based on non-probability quota sampling. Data were collected using a questionnaire including the marketing mix components of which the validity and reliability was confirmed. The data were analyzed using the SPSS V.16 software with a multiple regression hypothesis. Results: The results showed that among the components of the services marketing mix, the price had the maximum effect (49.2%) and the physical assets had the minimum effect (14.1%) on patients` tendency to public hospitals. On the other hand, staff had the maximum effect (48.4%) and the promotion had the minimum effect (18.6%)on the patients` tendency to private hospitals. Conclusion: Price is a determining factor in patient's tendency to refer to public hospitals compared to private hospitals because of delivering services with lower rates. On the other hand, the main reason for patient's reference to private hospitals is their staff that could be due to their sense of responsibility, accuracy and speed in providing services to patients